Makna Voice Over dalam Pemberitaan Feature di Televisi - Nova Shafira Sunarto Putri; Rita Gani (Jurnal Riset Jurnalistik dan Media Digital, 2022)
Abstract. Voice Over or what is known as VO is being discussed a lot, not only about the profession, but also from the industry side and the various voice over techniques used. Due to this phenomenon, many ordinary people try voice over from imitating, covering, voice over. challenges on instagram. From a journalistic point of view, voice over is also used in news programs, from various types of regular news programs, this research focuses on voice over features because it has more discussion, the way it is delivered, produces more diverse news using different voice colors, with the research subject being voice actors. overfeature news tvOne. This study is entitled The Meaning of Voice Over in Television Feature Reporting. The purpose of this study is to discuss the experiences of voice over talent from the journey of becoming voice over talent to the voice over production process on tvOne, to analyze the motives for becoming voice over talent feature news on tvOne, to find the meaning of voice over on tvOne news feature, to analyze self-representation as news voice over. This study uses a qualitative research method, Alfred Schutz's phenomenological approach to answer research questions. The results of the research in the experience of news voice over on tvOne that each informant has a different experience and it has been for many years, some have previous experience because they have served in the media before, have knowledge through training, have the ability to report or deliver news. Commonly used voice over techniques include articulation, emphasize, and intonation. The motives behind the voice over tvOne news in carrying out their work are dream motives, work experience motives, and interest motives. These motives are included in the because motive or past motives. Meanwhile, future motives or in order to motives are economic motives and learning motives. The self-representation of news voice over consists of two parts, namely the front stage and the back stage. The front stage for news voice overs is when they take voice over, voice according to the character of the feature or program script, do voice acting with an informative impression. Back stage for news voice over is script discussion with producer or scriptwriter, doing script or voice character research, practicing before doing voice over take. The meaning of voice over for news voice over is divided into five categories, namely, (1) Voice over and picture shows have the same value, (2) Voice has feelings and emotions (3) Voice over as a messenger (4) Voice over to channel interest and (5) Voice over as a learning medium. Abstrak. Voice Over atau yang dikenal VO sedang banyak diperbincangkan, tidak hanya seputar profesinya saja, tetapi dari sisi industri dan berbagai teknik-teknik voice over yang digunakan, adanya fenomena ini banyak orang awam mencoba-coba voice over dari meniru, meng-cover, voice over challenge di instagram. Dari sisi jurnalistik voice over pun digunakan pada program berita, dari berbagai jenis program berita reguler, penelitian ini fokus dalam voice over feature karena lebih banyak pembahasannya, cara penyampaiannya, menghasilkan berita yang lebih beragam dengan menggunakan warna suara yang berbeda, dengan subjek penelitian pengisi voice over feature news tvOne. Penelitian ini berjudul Makna Voice Over Dalam Pemberitaan Feature Di Televisi.Tujuan penelitian ini untuk membahas pengalaman para voice over talent dari proses perjalanan menjadi voice over talent sampai proses produksi voice over di tvOne, untuk menganalisis motif menjadi voice over talent feature news di tvOne, untuk menemukan makna dari voice over pada feature news tvOne, untuk menganalis representasi diri sebagai news voice over. Penelitian ini menggunakan metode penelitian kualitatif, pendekatan fenomenologi Alfred Schutz untuk menjawab pertanyaan penelitian. Hasil penelitian dalam pengalaman news voice over di tvOne bahwa setiap informan memiliki pengalaman yang berbeda dan sudah bertahun-tahun, ada yang memiliki pengalaman sebelumnya karena pernah bertugas di media sebelumnya, memiliki ilmu melalui pelatihan, memiliki kemampuan dalam reportase atau menyampaikan berita. Teknik voice over yang umum digunakan meliputi artikulasi, emphasize, dan intonasi. Motif yang menjadi latar belakang para news voice over tvOne dalam menjalankan pekerjaannya adalah motif mimpi, motif pengalaman pekerjaan, motif minat. Motif tersebut termasuk ke dalam because motive atau motif masa lalu. Sedangkan motif masa depan atau in order to motive yaitu motif ekonomi dan motif belajar. Representasi pada diri news voice over terdiri dari dua bagian yaitu front stage dan back stage. Front stage para news voice over adalah saat melakukan take voice over, menyuarakan sesuai karakter naskah feature atau program, melakukan voice acting bersuara dengan kesan informatif. Back stage para news voice over adalah diskusi naskah dengan produser atau penulis naskah, melakukan riset naskah atau karakter suara, berlatih sebelum melakukan take voice over. Makna voice over bagi news voice over dibagi menjadi lima kategori yakni, (1) Voice over dan tayangan gambar memiliki nilai yang sama, (2) Suara memiliki rasa dan emosi (3) Voice over sebagai penyampai pesan (4) Voice over untuk menyalurkan minat dan (5) Voice over sebagai media belajar.